Religious Moderation in Constantinople in the Resolution of Political Conflicts in the 14th Century - Muhimmatul Mukaromah; Lutfiana Dwi Mayasari; Shereeza Mohamed Saniff (AL-TAHRIR, 2023)
The Islamic conquest of Constantinople in the 14th century is a captivating historical episode in history that continues to intrigue historians. It stands out due to the involvement of two major world religions - Islam and Christianity. Furthermore, this conquest marked the end of the Roman civilization. One notable aspect of this conquest was the harmonious relationship between Muslims and Christians, which persisted before and after the event. This study aims to explore the implementation of religious moderation in Constantinople to resolve political conflicts. Adopting a historical methodology, the research collects data through extensive documentation and literature studies, employing a socio-political approach. The findings highlight that religious moderation played a crucial role in conflict resolution during the 14th century in Constantinople. The concept of religious moderation was not only applied before the conquest, but also after it. Before the conquest, the value of moderation was demonstrated through peaceful negotiations between the Islamic kingdom and the Catholic prelate in Rome. Several treaties were agreed upon, emphasizing the importance of faith and peaceful dialogue over resorting to military confrontation. Following the conquest, Sultan Muhammad al-Fatih exemplified religious moderation by engaging in negotiations with the inhabitants of Hagia Sophia. They agreed an agreement allowing Christians to continue practicing their faith despite being under Islamic rule. Additionally, al-Fatih displayed respectful treatment towards the prelate and Christian warlords, further exemplifying the value of moderation. The findings of this study shed light on the significance of religious moderation in resolving conflicts and offer a fascinating insight into the history of Constantinople during this period